Penggunaan AI (Artificial Intelligence) dalam Pendidikan Islam di Indonesia - Deasy Eka Saputri; M. Guntur Alting (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The advancement of science and technology has significantly impacted various sectors, including Islamic education. This study explores the integration of Artificial Intelligence (AI) in Islamic educational institutions, particularly in Islamic boarding schools, high schools with Islamic integration (SMA IT), and Islamic boarding schools. The use of AI in these institutions enhances the learning process, making it more efficient and effective. This paper discusses the development and challenges of incorporating AI in Islamic education, the role of technology in modernizing educational practices, and the implications for students' learning outcomes.